Analysis of Some Immunological Aspects of Joint Infections Developed as a Result of Intra-Articular Glucocorticoid Injection - DekhtiarenkoN.О.; Panchenko, L.M.; Hrytsai, M.P.; Linenko, O.M.; Sabadosh, V.I.; Salmanova, K.M. (TERRA ORTHOPAEDICA, 2021)
Summary. The work is devoted to the studies of immune status of patients with infectious complications after local glucocorticoid injections. Objective: to assess the state of the immune system of patients with infectious complications after local glucocorticoid injections, to monitor the dynamics of immunological parameters before and after sanitizing surgical treatment, and to reveal factors that are important for predicting the course of the disease and treatment results. Materials and Methods. The immune status of 26 patients with purulent inflammatory processes after local glucocorticoid injections in rheumatoid arthritis, deforming osteoarthritis, and chronic synovitis was studied. Immunological, hematological, and statistical research methods were used. Results. Changes of immunity factors as well as hematological parameters were revealed: a decrease in the content of T-lymphocytes (CD3+), T-helpers (CD4+), T-suppressors / cytotoxic lymphocytes (CD8+), immunoglobulins of classes A, M, and G; an increase in the levels of circulating immune complexes (СIC), the number of thrombocytes, erythrocyte sedimentation rate (ESR), and the reaction of the neutrophil leukocytes. It has been shown that the improvement of the immune status and the decrease in the level of inflammatory reactions after the sanitizing surgical intervention occurs slowly, which requires the inclusion of immunocorrective therapy in the treatment of such patients. Conclusions. Primary examination of patients before surgery for the purpose of sanitizing the infection showed that the local inflammatory process in the bones and joints occurs against the background of altered immunological and hematological parameters. Dynamic follow-up showed that we are dealing not only with a local process, but also with a systemic inflammatory response. A variant of the laboratory criterion for the course of infectious complications and the effectiveness of the treatment can be the determination in the dynamics of the content of T-lymphocytes and their subpopulations, the levels of the CIC, platelets and ESR.